Development and validation of a risk score to predict the probability of postoperative vomiting in pediatric patients: the VPOP score. Issue 9 (14th May 2014) - Bourdaud, Nathalie; Devys, Jean‐Michel; Bientz, Jocelyne; Lejus, Corinne; Hebrard, Anne; Tirel, Olivier; Lecoutre, Damien; Sabourdin, Nada; Nivoche, Yves; Baujard, Catherine; Orliaguet, Gilles A.; Lerman, Jerrold
Summary Background Few data are available in the literature on risk factors for postoperative vomiting (POV) in children. Objective The aim of the study was to establish independent risk factors for POV and to construct a pediatric specific risk score to predict POV in children. Methods Characteristics of 2392 children operated under general anesthesia were recorded. The dataset was randomly split into an evaluation set (n = 1761), analyzed with a multivariate analysis including logistic regression and backward stepwise procedure, and a validation set (n = 450), used to confirm the accuracy of prediction using the area under the receiver operating characteristic curve (ROCAUC), to optimize sensitivity and specificity. Results The overall incidence of POV was 24.1%. Five independent risk factors were identified: stratified age (>3 and <6 or >13 years: adjusted OR 2.46 [95% CI 1.75–3.45]; ≥6 and ≤13 years: aOR 3.09 [95% CI 2.23–4.29]), duration of anesthesia (aOR 1.44 [95% IC 1.06–1.96]), surgery at risk (aOR 2.13 [95% IC 1.49–3.06]), predisposition to POV (aOR 1.81 [95% CI 1.43–2.31]), and multiple opioids doses (aOR 2.76 [95% CI 2.06–3.70], P < 0.001). A simplified score was created, ranging from 0 to 6 points. Respective incidences of POV were 5%, 6%, 13%, 21%, 36%, 48%, and 52% when the risk score ranged from 0 to 6. The model yielded a ROCAUC of 0.73 [95% CI 0.67–0.78] when applied to the validation dataset. Conclusions Independent risk factors for POV were identified and used to create a new score to predict which children are at high risk of POV.